The Pathology of Morphine-Inhibited Nerve Repair and Morphine-Induced Nerve Damage Is Mediated via Endoplasmic Reticulum Stress - Liu, Jie; Yi, Shanyong; Shi, Weibo; Zhang, Guozhong; Wang, Songjun; Qi, Qian; Cong, Bin; Li, Yingmin (Frontiers in Neuroscience, 2021)
Objective The aim of the present study was to observe the pathological damage in the cerebral cortex of rats under acute morphine exposure (AME) and different durations of morphine dependence (MD), explore whether endoplasmic reticulum stress (ERS) is involved in the damage process, and assess the effect of morphine exposure on the proliferation and differentiation of newborn neurons. Methods Rat models of AME and different durations of MD were established. Pathological changes in cortical neurons were assessed by hematoxylin and eosin (H&E) and thionine staining. The expression of nuclear receptor-related factor 1 (NURR1) and that of the ERS-related proteins glucose-regulated protein 78 (GRP78), p-eIF2α, activating transcription factor 6 (ATF6), and CHOP in cortical neurons was assessed by immunohistochemistry. Double immunofluorescence labeling was used to observe the expression of Ki-67. Results H&E and thionine staining revealed that AME resulted in pyknotic changes in cortical neurons. With prolonged morphine exposure, the number of pyknotic neurons was significantly increased, the protein expression of Ki-67 and NURR1 was significantly decreased, and the protein levels of GRP78, p-eIF2α, ATF6, and CHOP showed marked dynamic changes. Conclusion AME and different durations of MD caused varying degrees of pathological changes in the cortex. Furthermore, the dynamic changes observed in ERS-related protein expression suggested that ERS may be associated with cortical injury. Different durations of MD inhibited the proliferation, differentiation, and migration of newborn neurons, which may affect the nerve repair process after injury.